Universal Follow-Up After Extracorporeal Membrane Oxygenation: Baby Steps Toward Establishing an International Standard of Care - MacLaren G (Baltimore, MD : Lippincott Williams & Wilkins, c2000-, 2018)
10.1097/PCC.0000000000001317